Socio cultural and linguistic incompatibility and significance of culture in second language teaching - Lal, Sam Mohan (Journal of Modern Languages, 2017)
The relationship between culture and language has been known to the researchers. But, this relationship became more prominent and used extensively during language research in the 1990s with the turn and advent of modem linguistics. Since then specific attention was paid to this relationship even though studies on culture date back to antiquity. (Brooks, 1975). If this relationship between language and culture is not properly handled in the class room, there will be lot of cultural incompatibility during communication. Demen's work (1987) approached the influence of culture on interaction and communication. She urges the language teachers to become the ethnographers of their own student’s culture to provide insights into learner knowledge and expectations. Allen (1985) says that the goal of having culture syllabus is not to force the students to change their cultural identity but it is to enable them understand the complexity of culture and that is demonstrated in every way of life. From the above works and from the experience of the second language teachers It is clear that in order to have effective communication and to avoid communicative incompatibility, it is inevitable to include culture teaching in the language classes. This paper deals with some of the problems faced by the mother tongue speakers of Tamil while learning Malayalam as the second language in India. Also, this paper tries to give some suggestions to the teachers to teach culture in a class room.